The battlemage / 3. - Matharu, Taran (Matharu, Taran. Summoner, 2017)
"Fletcher and his classmates from Vocans Academy--including the elf Sylva and the dwarf Othello--travel through the ether, where they must pursue a mortally dangerous quest to rebuild their world and broker peace. As he leads a small army of soldiers, Fletcher will face his biggest challenge yet: his nemesis, the albino orc, Khan, who seeks to destroy everything Fletcher loves."--Dust jacket.